2023
DOI: 10.7554/elife.84822
|View full text |Cite
|
Sign up to set email alerts
|

Pupil size reflects activation of subcortical ascending arousal system nuclei during rest

Abstract: Neuromodulatory nuclei that are part of the ascending arousal system (AAS) play a crucial role in regulating cortical state and optimizing task performance. Pupil diameter, under constant luminance conditions, is increasingly used as an index of activity of these AAS nuclei. Indeed, task-based functional imaging studies in humans have begun to provide evidence of stimulus-driven pupil-AAS coupling. However, whether there is such a tight pupil-AAS coupling during rest is not clear. To address this question, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Indeed, pupil size and pre-stimulus alpha power are believed to be two sides of the same coin: high arousal states go hand in hand with alpha power suppression and pupil dilation (Aston-Jones & Cohen, 2005; Reimer et al, 2016), and alpha power and pupil diameter appear to be coupled during quiet wakefulness (Montefusco-Siegmund et al, 2022). Yet, there also appear to be dissociations between the effects of pre-stimulus alpha power and pupil-linked arousal on behavior (Lloyd et al, 2023), and there is evidence that suggests that the relationship between alpha power and pupil size is nonlinear (T. Pfeffer et al, 2021; Podvalny et al, 2021). Moreover, a set of studies indicates that pre-stimulus alpha oscillations drive decision bias by modulating neuronal excitability (Iemi et al, 2017, 2022; Kloosterman et al, 2019; Samaha et al, 2020), rather than perceptual sensitivity as we report here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, pupil size and pre-stimulus alpha power are believed to be two sides of the same coin: high arousal states go hand in hand with alpha power suppression and pupil dilation (Aston-Jones & Cohen, 2005; Reimer et al, 2016), and alpha power and pupil diameter appear to be coupled during quiet wakefulness (Montefusco-Siegmund et al, 2022). Yet, there also appear to be dissociations between the effects of pre-stimulus alpha power and pupil-linked arousal on behavior (Lloyd et al, 2023), and there is evidence that suggests that the relationship between alpha power and pupil size is nonlinear (T. Pfeffer et al, 2021; Podvalny et al, 2021). Moreover, a set of studies indicates that pre-stimulus alpha oscillations drive decision bias by modulating neuronal excitability (Iemi et al, 2017, 2022; Kloosterman et al, 2019; Samaha et al, 2020), rather than perceptual sensitivity as we report here.…”
Section: Discussionmentioning
confidence: 99%
“…These neuromodulators have widespread effects throughout the brain, from controlling global cortical dynamics (e.g., low frequency power (McGinley, Vinck, et al, 2015)) to tuning the gain of sensory processing (McGinley, David, et al, 2015; Reimer et al, 2014; Vinck et al, 2015). Pupil dilation reflects the activity of neuromodulatory nuclei and can therefore be used to non-invasively approximate fluctuations in arousal state (de Gee et al, 2017; Joshi et al, 2016; Lloyd et al, 2023; Murphy, O’Connell, et al, 2014; Reimer et al, 2016; Strauch et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have reported a correlation between pupil diameter and activity of the locus coeruleus, the main source of noradrenaline in the brain (Joshi & Gold, 2019; Joshi et al, 2016; Murphy, O’Connell, O’Sullivan, Robertson, & Balsters, 2014), this link has recently come under debate (Megemont, McBurney-Lin, & Yang, 2022). Pupil size also correlates with the trial-by-trial BOLD signal activity in other brain stem nuclei, specifically the dopaminergic ventral tegmental area and substantia nigra, at least during rest (Lloyd, de Voogd, Mäki-Marttunen, & Nieuwenhuis, 2023). It might be interesting to consider the possibility that the action-induced modulation of pupil dilation in this study in fact reflect dopaminergic activity (Varazzani et al, 2015; Walton & Bouret, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, exploitation refers to a behavioral mode characterized by focus on a single task. These behavioral modes correlate with the activity of the locus coeruleus (LC), which in turn is believed to be strongly correlated with pupil size, such that high levels of LC activity are associated with dilated pupils (De Gee et al, 2017; Joshi & Gold, 2020; Liu et al, 2017; Lloyd et al, 2023). Therefore, pupil size, in this context often referred to as pupil‐linked arousal, is often used as a proxy for LC activity to study predictions of the AGT.…”
Section: Pupil Size Is a Vital Component Of Visual Cognitionmentioning
confidence: 99%